Lost and Found: Coffea stenophylla and C. affinis, the Forgotten Coffee Crop Species of West Africa - Davis, Aaron P.; Gargiulo, Roberta; Fay, Michael F.; Sarmu, Daniel; Haggar, Jeremy (Frontiers in Plant Science, 2020)
Two species, Coffea arabica and C. canephora, are used to produce the world’s coffee, and serve the coffee sector admirably. However, various challenges at the production (farm) level, including the increasing prevalence and severity of disease and pests and climate change, indicate that the coffee crop portfolio needs to be diversified in order to ensure resilience and sustainability. In this study we use a multidisciplinary approach (herbarium and literature review, fieldwork and DNA sequencing) to elucidate the taxonomic identities, agronomic attributes and whereabouts of two poorly known coffee crop species, C. affinis and C. stenophylla. We show that despite widespread, albeit small-scale, use as a coffee crop species across Upper West Africa, (and further afield) more than 100 years ago , these species are now rare in the wild and in cultivation. Fieldwork enabled us to rediscover C. stenophylla in Sierra Leone, which previously had not been recorded in the wild there since 1954. We confirm that C. stenophylla is an indigenous species in Guinea, Sierra Leone, and Ivory Coast, and show that C. affinis is indigenous in Guinea and Ivory Coast. Both species are likely to be threatened with extinction in the wild, particularly in Guinea. DNA sequencing using plastid and ITS markers was used to: confirm the identity of museum and field collected samples of C. stenophylla; demonstrate the use of plastid and nuclear markers to identify F1 and early-generation interspecific hybrids; identify the hybrid C. liberica x C. stenophylla; and reveal that C. liberica is non-monophyletic and likely to represent more than one species. Contrary to contemporary opinion, we could find no evidence of hybrid status for C. affinis, although the taxonomic identity of this species remains unclear. Sequencing analyses also show that hybridization is possible across all the major short-styled Africa Coffea species, i.e. Coffee Crop Wild Relative Priority Groups I and II. Coffea affinis and C. stenophylla may possess traits useful for coffee crop plant development, including taste differentiation, disease resistance, and climate resilience; these attributes would be best accessed via breeding programmes although these two species may have potential as crops with minimal domestication.